Stages of the Creation of the Universe: Tahlili QS Studies. Al-A'raf Verse 54 According to the Tafsir of Science - Rizki Rizki; John Supriyanto; RA. Erika Septiana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to analyze the stages of the creation of the universe through a tahlili study of QS. Al-A'raf verse 54 from the perspective of scientific interpretation. The research method used is a qualitative method with a library research approach, where data is collected from primary sources in the form of classical and contemporary tafsir books, as well as secondary sources in the form of scientific journals and books relevant to the theme of the creation of the universe. Data analysis was carried out using the tahlili method which includes linguistic studies, asbabun nuzul, munasabah of verses, and comparison of interpretations from five selected tafsir books, namely Tafsir Al-Azhar, Tafsir Al-Mishbah, Tafsir Al-Maraghi, Tafsir Al-Munir, and Tafsir Ibnu Katsir. The research findings show that QS. Al-A'raf verse 54 is a fundamental foundation in understanding the concept of the creation of the universe according to Islam, which affirms that Allah SWT is the sole Creator who created the heavens and the earth in six periods gradually with full wisdom. Creation in six periods can be correlated with the stages of cosmic evolution in modern science without substantial contradiction. The mufassirs agree that this verse contains theological, epistemological, spiritual, and ethical dimensions that are highly relevant to the contemporary context. The implications of this research indicate that an integrative approach between Quranic interpretation and modern science can strengthen the faith of Muslims while providing an intellectual foundation for constructive dialogue between religion and science in understanding the origin and structure of the universe.